Ethical branding - Patterson, Anthony (Henry Stewart Talks, 2008)
History of branding ethics, Greenwashing, Case studies: Ben & Jerry's and Marks & Spencer, Why build ethical brands?, Recognising, analysing and resolving ethical dilemmas